Controversies in depression management (Adis international, 2000)
Looks at some of the current controversies in the management of depression, with special emphasis on drug treatment. Covers areas such as the onset of action of antidepressants, their mode of action and possible side effects, and more. Some articles have been previously published in Adis International's peer-reviewed journals.